A comprehensive in silico and invitro analysis revealed the diagnostic, prognostic and therapeutic potential of GNAI family genes in colon adenocarcinoma (COAD) - Bei Wang; Fan Zhu; Yingying Chen (Hereditas)
Abstract Introduction Guanine nucleotide-binding protein alpha inhibiting activity polypeptides (GNAI1, GNAI2, and GNAI3) play critical roles in cell cycle regulation, intracellular signaling, and immune modulation. However, their contribution to colorectal adenocarcinoma (COAD) pathogenesis remains poorly defined. This study aimed to comprehensively evaluate the diagnostic, prognostic, and therapeutic relevance of GNAI genes in COAD through integrated in silico and in vitro analyses. Methods mRNA and protein expression profiles of GNAI1, GNAI2, and GNAI3 were analyzed using TCGA, OncoDB, HPA databases, and RT-qPCR analysis across COAD cell lines. Genetic and epigenetic alterations were assessed using UALCAN, cBioPortal, and GSCA databases. Prognostic significance was evaluated through Kaplan–Meier survival and GENT2 databases. Potential miRNA regulators were identified via TargetScan and quantified using TaqMan assays. Immune interactions, immune infiltration, and drug sensitivity were examined using TISIDB and GSCA platforms. Functional effects of GNAI1 and GNAI2 overexpression were tested in SW480 and HCT116 cell lines using proliferation, colony formation, and wound healing assays. Results GNAI1, GNAI2, and GNAI3 were significantly downregulated in both COAD tissues and cell lines. This downregulation correlated with promoter hypermethylation, CNV deletions, and reduced patient survival. ROC analysis indicated better diagnostic potential, particularly for GNAI2 (AUC = 0.83). Pathway analysis revealed suppression of DNA damage and cell cycle regulatory pathways and activation of EMT-related signaling. Upregulated miRNAs—hsa-miR-133a-3p-1, hsa-miR-138-5p, and hsa-miR-141-3p—were identified as direct regulators, exhibiting strong diagnostic capacity. Immune profiling showed that GNAI genes were differentially expressed across immune subtypes, negatively correlated with immune inhibitors, and positively associated with stimulators. Overexpression of GNAI1 and GNAI2 significantly inhibited COAD cell proliferation, clonogenic potential, and migration. Conclusion This study reveals the tumor-suppressive function of GNAI1, GNAI2, and GNAI3 in COAD through genetic, epigenetic, and miRNA-mediated regulation. Their downregulation is associated with poor prognosis, altered immune landscape, and therapy resistance. Restoration of GNAI function represents a promising avenue for diagnostic and therapeutic intervention in colorectal cancer. Clinical trial number None.